2007
DOI: 10.1007/s11274-007-9609-y
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a glycolipid biosurfactant from Bacillus megaterium using economically cheaper sources

Abstract: Criteria selected for screening of biosurfactant production by Bacillus megaterium were hemolytic assay, bacterial cell hydrophobicity and the drop-collapse test. The data on hemolytic activity, bacterial cell adherence with crude oil and the drop-collapse test confirmed the biosurfactant-producing ability of the strain. Accordingly, the strain was cultured at different temperatures, pH values, salinity and substrate (crude oil) concentration in mineral salt medium to establish the optimum culture conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
56
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 41 publications
13
56
0
1
Order By: Relevance
“…The most studied low-molecular-weight biosurfactant compounds are lipopeptides and glycolipids. Lipopeptides are mainly produced by members of the Bacillus species; they are composed of different families and each family is constituted of several variants, which can differ in their fatty acid chain and their peptide moiety (Dastgheib et al, 2008;Jacques, 2010;Thavasi et al, 2008Thavasi et al, , 2011.…”
Section: Low Molecular Weight Compounds 211 Lipopeptidesmentioning
confidence: 99%
“…The most studied low-molecular-weight biosurfactant compounds are lipopeptides and glycolipids. Lipopeptides are mainly produced by members of the Bacillus species; they are composed of different families and each family is constituted of several variants, which can differ in their fatty acid chain and their peptide moiety (Dastgheib et al, 2008;Jacques, 2010;Thavasi et al, 2008Thavasi et al, , 2011.…”
Section: Low Molecular Weight Compounds 211 Lipopeptidesmentioning
confidence: 99%
“…Several renewable substrates from various sources, particularly from well-known industrial wastes have been intensively studied for microorganism cultivation and biosurfactant production on a laboratory scale (Daniel et al, 1998;Solaiman et al, 2004;Felse et al, 2007;Thavasi et al, 2008;Sitohy et al, 2010;Parekh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many published studies reported the successful isolation of biosurfactant producing organisms from soil polluted with hydrocarbons or mineral oils (Mukherjee, et al, 2009;Mulligan, 2005). We were successful in isolating bacteria with the ability to produce biosurfactants from the soil samples collected from garage oil contaminated soils like many other scientists have chosen the same source for soil collection, (Thavasi, et al, 2008 andSaravanan, et al, 2012).…”
Section: Screening Of Biosurfactant Producing Bacteria In Msm Medimentioning
confidence: 94%